Use of stereolithographic cutting guides in corrective (wedge) Lefort I osteotomy - Seeberger, Robin; Scherfler, Sebastian; Freier, Kolja; Thiele, Oliver C. (The British journal of oral & maxillofacial surgery, 2011)
Intraoperative navigation is a helpful tool in complex anatomical regions or procedures. The mobility of the mandible in relation to the skull base limits the use of navigation tools on the lower jaw if the reference device is installed on the forehead. A new workflow that allows navigation-assisted sagittal split osteotomy in orthognathic surgery using a separate non-invasive mandibular registration technique has been developed. An evaluation of accuracy in different anatomical regions and with different registration techniques was performed on skull models and skulls with movable mandibles. The mean inaccuracy was 1.51 mm, with no significant difference between anatomical sites. Using a splint-based reference device allows the movable mandible to be registered independently from the midface. Registration using metal points in the splint provides higher accuracy than using interdental anatomical landmarks. The workflow could be transferred successfully to patient treatment. Navigation-assisted osteotomy by Obwegeser-Dal Pont technique was performed without any complication in six patients. The mean deviation from the planned osteotomy line was 1.52 mm. The navigated sagittal split ramus osteotomy seems to be a suitable technique to increase patient safety. - Appropriate positioning of the maxilla is critical in orthognathic surgery. As opposed to splint-based positioning, navigation systems are versatile and appropriate in assessing the vertical dimension. Bulk and disruption to the line of sight are drawbacks of optical navigation systems. - Our aim was to develop and assess a novel navigation system based on electromagnetic tracking of the maxilla, including real-time registration of head movements. Since the software interface has proved to greatly influence the accuracy of the procedure, we purposely designed and evaluated an original, user-friendly interface. - A sample of 12 surgeons had to navigate the phantom osteotomized maxilla to eight given target positions using the software we have developed. Time and accuracy (translational error and angular error) were compared between a conventional and a navigated session. A questionnaire provided qualitative evaluation. - Our system definitely allows a reduction in variability of time and accuracy among different operators. Accuracy was improved in all surgeons (mean terror difference = 1.11 mm, mean aerror difference = 1.32°). Operative time was decreased in trainees. Therefore, they would benefit from such a system that could also serve for educational purposes. - The majority of surgeons who strongly agreed that such a navigation system would prove very helpful in complex deformities, also stated that it would be helpful in everyday orthognathic procedures. - This review summarises all orthognathic and related papers published between January 2011 and December 2012 in the British Journal of Oral and Maxillofacial Surgery (BJOMS). A total of 36 articles were published, a high proportion of which (78%) were full-length papers. The remainder consisted of short communications and technical notes. The topics included operative planning and postoperative outcomes, and there was a strong focus on distraction osteogenesis. There were fewer orthognathic articles published in BJOMS than articles on other subspecialties such as trauma or head and neck oncology. Only 8 (29%) of the full-length articles were prospective studies or randomised trials, which highlights a need for well-designed clinical studies in orthognathic research. - Cette publication présente une procédure nouvelle de chirurgie guidée, totalement assistée depuis la simulation informatique des ostéotomies jusqu’au contrôle de leur execution chirurgicale à l’aide des guides de coupe préfabriqués par stéréolithographie et des miniplaques préfabriquées avant l’acte chirurgical par fusion sélective par laser de lits de poudre de titane. Les principes qui régissent la conception et la fabrication industrielle de ce nouveau type de miniplaques d’ostéosynthèse sont présentés. L’ensemble de la procédure est décrite étape par étape en se basant sur plusieurs cas représentatifs de dysmorphoses dento-maxillofaciales. Les premiers résultats encourageants font apparaitre l’étendue des indications de cette nouvelle technologie en chirurgie cranio-maxillofaciale quel que soit le type de l’ostéotomie réalisée et en chirurgie plastique reconstructrice. - We present a new model of guided surgery, exclusively using computer assistance, from the preoperative planning of osteotomies to the actual surgery with the aid of stereolithographic cutting guides and osteosynthetic miniplates designed and made preoperatively, using custom-made titanium miniplates thanks to direct metal laser sintering. We describe the principles that guide the designing and industrial manufacturing of this new type of osteosynthesis miniplates. The surgical procedure is described step-by-step using several representative cases of dento-maxillofacial dysmorphosis. The encouraging short-term results demonstrate the wide range of application of this new technology for cranio-maxillofacial surgery, whatever the type of osteotomy performed, and for plastic reconstructive surgery. - La navigation chirurgicale est un outil informatique destiné à aider le chirurgien à atteindre, en cours d’intervention, une cible préalablement déterminée. Cette technique peut être appliquée au positionnement des fragments osseux dans le cadre de la chirurgie orthognathique. Elle est actuellement peu utilisée en raison de l’absence de système commercialement disponible, spécifiquement dédié à ce type de chirurgie. Le but de notre travail a été de décrire les différentes solutions techniques utilisables en chirurgie orthognathique et de rapporter notre expérience de la navigation dans le positionnement des maxillaires lors des ostéotomies maxillomandibulaires. - Computer-assisted navigation is a tool that allows the surgeon to reach intraoperatively a previously defined target. This technique can be applied to the positioning of bone fragments in orthognathic surgery. It is not used routinely yet because there are no specifically dedicated systems available on the market for this kind of surgery. The goal of our study was to describe the various systems that could be used in orthognathic surgery and to report our experience of computer-assisted surgery in the positioning of the maxilla during maxillomandibular osteotomies. - The British Journal of Oral and Maxillofacial Surgery (BJOMS) publishes many types of papers including original articles, review articles, and short communications. Many of the latter are isolated case reports of rare or interesting diseases or of difficult or unexpected complications. While case reports are sometimes considered to be of little educational or clinical value, and as such do little to advance medical knowledge, they do have an important role, and many trainees begin their publishing careers writing such papers. There is increasing pressure for space in paper medical journals and, for this reason, some journals either limit or do not publish short publications in print copy but instead put them online. - Using established criteria, we previously evaluated all 142 short communications published in the BJOMS during 2008-2009 and found that 48% of them had little or no educational value. As a result, the editorial board of BJOMS took the decision to publish most short communications online only. We have now analysed 48 short communications that were published online only during 2010-2011. Most (80%) were single case reports that covered virtually the whole remit of the specialty, and over half (56%) were published by authors based in the UK. While many of these papers did not add important new information to existing knowledge, these types of article are clearly of value both for trainees and for experienced surgeons. We think that these should continue to be supported as, in addition to their educational value, they are an excellent way for trainees to start to write.
Gesehen am 31.10.2022